The Influence of Chocolate Snack Packaging Design (Special Edition) on the Interests of Young Girls - Ayureza Kenusa Yusuf; Ahmad Syarief (PT Publikasiku Academic Solution, 2023)
This study discusses and analyzes the visual design of chocolate snack packaging and relates it to the buying interest of adolescents. Teenagers are a group of people who are in the process of growing and entering the adult stage. This makes teenagers have thoughts that continue to develop and change their mindset in terms of consumption. On the other hand, chocolate snack products are an important industry in Indonesia. With a large population in Indonesia, large cocoa production, and high levels of chocolate consumption, Indonesia is ranked 6th on a global scale. In this study, the approach was carried out quantitatively and analyzed descriptively. Data collection was carried out through literature studies and surveys of young respondents aged 17-25 years who live in Bandung and consume chocolate snacks. The results of this study indicate that the visual design of chocolate snack packaging can encourage adolescent buying interest, but it is the brand indicator that is the most significant driver of purchase interest